2024
DOI: 10.3847/1538-4357/ad2dfe
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-relativistic Electron Acceleration during High-intensity Long-duration Continuous Auroral Electrojet Activity Events

Rajkumar Hajra,
Bruce T. Tsurutani,
Quanming Lu
et al.

Abstract: Magnetospheric relativistic electrons are accelerated during substorms and strong convection events that occur during high-intensity long-duration continuous auroral electrojet activity (HILDCAA) events, associated with solar wind high-speed streams (coming from coronal holes). From an analysis of ∼2–20 MeV electrons at L ∼ 2–7 measured by the Van Allen Probe satellite, it is shown that ∼3.4–4.1 days long HILDCAA events are characterized by ∼7.2 MeV electron acceleration in the L ∼ 4.0–6.0 region, which occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 108 publications
(132 reference statements)
0
1
0
Order By: Relevance
“…It has been noted that relativistic magnetospheric electrons are detected predominately during this phase of the solar cycle (Baker et al, 1990;Li et al, 2001). Hajra et al (2015Hajra et al ( , 2024 have indicated that the acceleration of these relativistic electrons are associated with chorus (Horne et al, 2005;Thorne et al, 2013) during HILDCAA events. Allen et al (1989) showed that the magnetopause moved inside geostationary orbit (L = 6.6) during 13 and 14 March using GOES 7 and GOES 6 magnetic field observations.…”
Section: Geomagnetic Storms and Substormsmentioning
confidence: 99%
“…It has been noted that relativistic magnetospheric electrons are detected predominately during this phase of the solar cycle (Baker et al, 1990;Li et al, 2001). Hajra et al (2015Hajra et al ( , 2024 have indicated that the acceleration of these relativistic electrons are associated with chorus (Horne et al, 2005;Thorne et al, 2013) during HILDCAA events. Allen et al (1989) showed that the magnetopause moved inside geostationary orbit (L = 6.6) during 13 and 14 March using GOES 7 and GOES 6 magnetic field observations.…”
Section: Geomagnetic Storms and Substormsmentioning
confidence: 99%